EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DAN TIPE TWO STAY TWO STRAY (TSTS) TERHADAP HASIL BELAJAR IPA SISWA SMP NEGERI 1 BANGUNTAPAN BANTUL - Siti Samsiyah (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2016)
The study population was all students of class VII lesson consisting of 8 classes with a number of 216 students. Samples were taken by selecting random sampling. Data were taken with the engineering tests and documentation. Test validity with product moment correlation, from about 30 obtained 26 valid items and 4 in the fall. Test reliability using the KR - 20, obtained r count = 0.938, when compared with r table 5 % = 0.361, mean science achievement test is reliable. Techniques of data analysis using t-test before the data is analyzed first tested the requirement analysis that uses the distribution normality test and Chi-square test of homogeneity of variance using the F test. Descriptive research results show that the tendency of science learning of seventh-grade students are taught using cooperative learning model type jigsaw with 22.596 included in the category of very high and is taught using a type two stay two stray with on the everage 20.8148 included in the category of very high. Comparatively, there is a significant difference between the use of science learning outcomes cooperative learning model type jigsaw and type two stay two stray odd semesters of seventh-grade students of SMP Negeri 1 Banguntapan. It is shown from the results obtained by t-test = 2.383 where the value is greater than ttable5 % = 2.00 with db 52. By looking at the mean of the jigsaw cooperative learning model is higher than with the type two stay two strays. In other words, jigsaw cooperative learning model more effectively improves science learning outcomes compared with type two stay two strays.